Nurses’ Perception, Knowledge and Information Sources on Climate Change and Health at Dow University Hospital Karachi - Nazeer Ali Buriro; Sheh Mureed; Ramesh Kumar; Faheem Ahmed; Khadim Hussain; Amir Fatima (JLUMHS, 2018)
OBJECTIVE: To assess the knowledge, perception and information sources of nurses about climate change. METHODOLOGY: A cross sectional study conducted with total number of 105 respondents and duration of 03 months of 2016 at Dow University Hospital Karachi. Study population consisted of nurses and nursing management. Data collected through structured questionnaire. Data was analyzed using frequencies, percentages and associations. Institutional Review Board by Health Services Academy Ethically approved this study. Written consent from participants was taken prior to collect the data. RESULTS: Most of the nurses 96(94.4%) considered that air pollution affects their health. 74(70.5%) were known flooding as one of the adverse effects of climate change, academic qualification age and designation shown association at α =0.05 and CI: 95%. Over than 78% stated that social media was source of their information. The second most source was 67.6% national or international media. CONCLUSION: Majority of the nurses has insufficient knowledge and weak perception regarding adverse health effects of climate change, main sources of information were social media. Nurses knowledge can be enhance through in-house trainings and up gradation of the nursing curriculum.